2019
DOI: 10.3390/ma12213546
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hydrophobic Ni Surface by Chemical Etching

Abstract: Hydrophobic surfaces were successfully fabricated on pure nickel substrates by a one-step chemical etching process with different acidic solutions. The static water contact angle (SCA) of the etched Ni surfaces reached higher than 125°, showing excellent hydrophobicity. The examination of surface chemical compositions implied that there were almost no polar moieties on the surface after chemical etching, except part of the surface was oxidized. After chemical etching, the nickel surfaces became much rough with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Different studies have demonstrated that surfaces incorporating hydrophilic groups can exhibit super hydrophobic characteristics, underscoring the pivotal role of microstructures in determining the hydrophobicity of a surface. 58–61 In line with these findings, our experimental results for the femtosecond laser modified surfaces provide further support as we showcase that the generation of highly roughened surfaces added to wave like periodic patterns can generate hydrophobic surfaces even when showing the incorporation of hydrophilic groups, as shown by our XPS results.…”
Section: Resultssupporting
confidence: 87%
“…Different studies have demonstrated that surfaces incorporating hydrophilic groups can exhibit super hydrophobic characteristics, underscoring the pivotal role of microstructures in determining the hydrophobicity of a surface. 58–61 In line with these findings, our experimental results for the femtosecond laser modified surfaces provide further support as we showcase that the generation of highly roughened surfaces added to wave like periodic patterns can generate hydrophobic surfaces even when showing the incorporation of hydrophilic groups, as shown by our XPS results.…”
Section: Resultssupporting
confidence: 87%
“…Recently, superhydrophobic materials prepared by etching, , electrochemical deposition, , spraying, , and hydrothermal methods , have found good industrial applications due to their special functions such as self-cleaning and scale inhibition . Oil–water separation is a typical application example of superhydrophobic materials .…”
Section: Introductionmentioning
confidence: 99%
“…With a high water contact angle (WCA, >150 • ), and a low sliding angle (SA, <10 • ), superhydrophobic surfaces, inspired by natural creatures, have attracted extensive attention in academia [1,2]. Many methods, such as electrospinning [3,4], sol-gel [5][6][7], etching [8][9][10], hydrothermal [11,12], self-assembly [13,14] and template methods [15,16], have been used to prepare superhydrophobic surfaces. With the development of superhydrophobic technology, a single superhydrophobic surface cannot meet our requirements.…”
Section: Introductionmentioning
confidence: 99%